Molecular Characterization Revealed the Role of Thaumatin-Like Proteins of Bread Wheat in Stress Response - Sharma, Alok; Sharma, Himanshu; Rajput, Ruchika; Pandey, Ashutosh; Upadhyay, Santosh Kumar (Frontiers in Plant Science, 2022)
Thaumatin-like proteins (TLPs) are related to the pathogenesis-related-5 (PR-5) family and involved in stress response. Herein, a total of 93 TLP genes were identified in the genome of Triticum aestivum. Further, we identified 26, 27, 39 and 37 TLP genes in the Brachypodium distachyon, Oryza sativa, Sorghum bicolor and Zea mays genomes for comparative characterization, respectively. They could be grouped into small and long TLPs with conserved thaumatin signature motif. Tightly clustered genes exhibited conserved gene and protein structure. The physicochemical analyses suggested significant differences between small and long TLPs. Evolutionary analyses suggested the role of duplication events and purifying selection in the expansion of the TLP gene family. Expression analyses revealed the possible roles of TLPs in plant development and abiotic and fungal stress response. Recombinant expression of TaTLP2-B in Saccharomyces cerevisiae provided significant tolerance against cold, heat, drought and salt stresses. The results depicted the importance of TLPs in cereal crops that would be highly useful in future crop improvement programs.